Pengaruh Fasilitas Kerja Dan Kesejahteraan Terhadap Kinerja Pegawai Penanganan Prasarana Dan Sarana Umum (PPSU) Pada Kelurahan Kedoya Selatan Di Jakarta Barat - Muhammad Sabila Akbar; Iman Syatoto (JURNAL ILMIAH EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2026)
Abstract The purpose of this study was to determine the Effect of Work Facilities and Welfare on the Performance of Public Infrastructure and Facilities Handling Employees (PPSU) in the South Kedoya Village in West Jakarta both partially and simultaneously. The method used is quantitative. The sampling technique used saturated sampling and obtained a sample of 76 respondents. Data analysis used validity tests, reliability tests, classical assumption tests, regression analysis, correlation coefficients, determination coefficients and hypothesis tests with the help of SPSS software version 26. The results of this study are that work facilities have a significant effect on employee performance with a determination coefficient value of 55.7% and the hypothesis test obtained t count> t table or (9.652> 1.992). Welfare has a significant effect on employee performance with a determination coefficient value of 39.6% and the hypothesis test obtained t count> t table or (6.971> 1.992). Work facilities and welfare simultaneously have a significant effect on employee performance with the regression equation Y = 18.905 + 0.079X1 + 0.529X2. The coefficient of determination is 56.2% while the remaining 43.8% is influenced by other factors. The hypothesis test obtained a calculated F value > F table or (46.848 > 2.730).